Insecticide susceptibility status and major detoxifying enzymes activity in Anopheles subpictus from Kasur, Pakistan. Issue 3 (18th February 2019) - Naeem, H.; Oneeb, M.; Ashraf, K.; Rashid, M. I.; Nazir, M. M.; Tabassum, S.
Abstract: Anopheles subpictus s.l . Grassi (Diptera: Culicidae) is a malaria vector in South Asia, where insecticides are the mainstay for vector control interventions. Information on any variation in metabolic enzyme levels in mosquitoes is helpful with respect to adapting alternative strategies for vector control. The scarce data on the biochemical basis of insecticide resistance in malaria vectors of Pakistan limit the available information for vector control interventions within the country. The insecticide susceptibility status and its biochemical basis against dichlorodiphenyltrichloroethane (DDT) (4%), deltamethrin (0.05%) and permethrin (0.75%) in An. subpictus s.l . collected from all Tehsils of district Kasur were evaluated. For this purpose, a World Health Organization susceptibility bioassay was performed followed by the detection of altered metabolic enzyme activity using biochemical assays. Similarly, a significant difference in knock‐down effect was observed among field collected and susceptible strain against all insecticides 24 h post exposure. The overall mean mortality rates of DDT, deltamethrin and permethrin were 27.86% [95% confidence interval (CI) = 29.65–26.06], 44.89% (95% CI = 46.23–43.54) and 78.82% (95% CI = 80.16–77.47), respectively. The biochemical assays revealed an elevated level of metabolic enzymes in the field population. The results provide evidence of resistance against organochlorine and pyrethroid groups in a field population of An. subpictus s.l . from district Kasur mediated by multiple metabolic mechanisms, including acetylcholinesterases, esterases, cytochrome P450 and glutathione S ‐transferases. Abstract : The present study provides baseline data regarding the insecticide susceptibility status and its biochemical basis against Anopheles subpictus s.l . from Kasur, Pakistan. The results provide evidence of resistance against organochlorine and pyrethroid groups in a field population of An. subpictus s.l . mediated by multiple metabolic mechanisms. The fragility of the current situation in district Kasur encourages further investigations in all parts of the country with respect to the resistance profiles of malaria vector(s) and their mapping.